Enhancing livelihood of small farmers through cultivation of Arka Prajwal variety of tuberose - Balakrishna, B; Atheequlla, G A; Nair, Sujatha A; Supriya, B B; Bharathi, Usha; Maheshwari, Uma; Kowsalya, K S (Indian Farming, 2022)
The farmers have adopted new tuberose hybrid of ICAR-IIHR, Bengaluru along with precision farming package, which resulted in enhancement of production, productivity and quality of flowers. Due to ease of transport and higher price and market demand, farmers earned higher gross and net-income. Since FFP had three folded plans for doubling the income through cost reduction, production enhancement and diversification of enterprises, scientists were able to meet these objectives through introduction of tuberose with precision farming in selected FFP villages, which also made a huge impact in terms of doubling of farmers income within two years, horizontal and vertical spreading of varieties and technologies, and ultimately sustainable livelihood to the farmers under Farmer FIRST Project.